Endoscopic management of foreign bodies in the upper gastrointestinal tract - Chaudhari, Sandip Kumar S.; Chaudhary, Sonalben M. (International Surgery Journal, 2020)
Background: Foreign body ingestion and food bolus impaction is a common clinical scenario and can present as an endoscopic emergency. Though majority of them pass spontaneously 10-20% require endoscopic intervention. Flexible endoscopy is recommended as therapeutic measure with minimal complications. The aim of our study is to present 5 years’ experience in dealing with foreign bodies in the upper gastrointestinal tract. Methods: Cases of foreign body ingestion admitted to department of general surgery from March 2015 to March 2020 were evaluated. The patients were reviewed with details on age, sex, type of FB, its location in gastrointestinal tract, treatment and outcome. Results: A total of 55 cases were studied. Age range was 1-85 years. Males were predominant 61.81%. Coins were found most commonly 63.6%. Esophagus was the commonest site of FB lodgement 70.9%. Upper esophagus being the most common 36.36%. Upper gastrointestinal flexible endoscopy was useful in retrieving FB in all the 55 cases. There were no complications throughout the study period. Conclusions: Flexible endoscopy should be used as definitive treatment and endoscopic treatment is safe and effective.